ANALISIS SYARIAH SEBAGAI KATALISATOR TERHADAP PERTUMBUHAN KAPITALISASI PASAR INDEKS SYARIAH DI BEI - Jauhari, Muhammad Sofwan (An Nawawi, 2024)
The growth of the sharia capital market in Indonesia reflects increasing investment interest based on sharia principles that emphasize justice, transparency, and ethical investment. The sharia capital market presents a unique appeal amid global economic uncertainty, offering greater stability compared to conventional markets. This study aims to analyze the role of sharia as a catalyst for the growth of market capitalization in sharia indices on the Indonesia Stock Exchange (IDX). The research methodology uses a literature review method by analyzing secondary data and relevant theories from publications by the Financial Services Authority (OJK) and previous research. The findings show that Indonesia’s sharia capital market has experienced significant capitalization growth despite challenges such as economic crises and the pandemic. Several sharia indices, such as the Jakarta Islamic Index (JII) and the Indonesia Sharia Stocks Index (ISSI), have recorded long-term upward trends, supported by restrictions on speculation and the prohibition of riba practices. Regulatory support from OJK, particularly through policies that expand the scope of the Sharia Securities List (DES), further strengthens this growth. The year-to-year increase in the number of sharia stocks indicates market resilience and growing public awareness of sharia-based investments. With promising prospects, the sharia capital market in Indonesia is expected to continue to develop as a catalyst in market capitalization, positively contributing to the national economy through productive capital flows aligned with sharia values.